Feasibility analysis of an exhaust gas waste heat driven jet-ejector cooling system for charge air cooling of turbocharged gasoline engines. (15th December 2015) - Zegenhagen, M.T.; Ziegler, F.
Highlights: Investigation of a compound system of a combustion engine and a cooling system. Determination of feasible charge air temperatures in the compound system. Analysis of thermal COP, hydraulic COP and cooling capacity of the system. Derivation of required exhaust gas conditions and resulting pressure losses. Evaluation of power densities, additional fuel consumption and multi-staging. Abstract: The present paper analyzes the feasibility of an exhaust gas driven jet-ejector cooling system for charge air cooling of turbocharged gasoline engines in addition to the conventional charge air cooler to increase the engine efficiency. Thereto, steady-state experiments of a jet-ejector cooling system and an exhaust gas heat exchanger prototype working with the refrigerant R134a are used to analyze the operation and control of the compound system and determine feasible cooling capacities, charge air temperatures, thermal COP th and hydraulic COP h . Moreover, the cooling system is rated regarding its power densities and engine backpressure. The exhaust gas waste heat recovery, system power densities, and engine backpressure are acceptable. However, the hydraulic COP h and the amount of reject heat need to be improved, necessitating for instance a multi-staging of the jet-ejection.